Biological Network Analysis: Trends, Approaches, Graph Theory, and Algorithms - Guzzi, Pietro Hiram; Roy, Swarup (Elsevier Science & Technology, 2020)
Biological Network Analysis: Trends, Approaches, Graph Theory, and Algorithms considers three major biological networks, including Gene Regulatory Networks (GRN), Protein-Protein Interaction Networks (PPIN), and Human Brain Connectomes.